Perceptions of Institutional Response to Sexual Assault Amongst College-Based Victim Advocates - Nightingale, Sarah D. (Journal of interpersonal violence, 2023)
Federal law in the United States mandates that institutions of higher education address sexual assault within their communities. Colleges and universities have increasingly hired full-time professionals to manage response efforts, including campus-based victim advocates. Campus-based advocates provide emotional support, help students access and understand report options, and ensure students receive appropriate accommodations. Very little is known about the experience or perceptions of campus-based victim advocates. In this study, 208 professional campus-based advocates from across the United States completed an anonymous online survey focused on their perceptions of campus response to sexual assault. Multiple regression analysis was applied to investigate how psychosocial factors (burnout, secondary trauma, and compassion satisfaction) and organizational factors (perceptions of leadership, organizational support, and community relational health) were associated with advocate perceptions of institutional response to sexual assault. Findings indicate that while advocates experience burnout and secondary trauma, and have lower than average compassion satisfaction scores, these psychosocial outcomes do not influence their perception of response efforts. However, all the organizational factors significantly contribute to how advocates view response. The more positively advocates viewed leadership, campus support, and relational health, the more positive they viewed the response efforts on campus. In order to improve response efforts, administrators should engage in meaningful training on sexual assault, include campus advocates in high-level discussions of campus sexual assault and ensure appropriate resources are provided to advocacy services.